A cultura de segurança: estudo com os profissionais da enfermagem em ambiente hospital - Bratz, Sílvia (2020)
The work environment of health organizations has a fundamental role in the quality and safety of health care and the nursing team contributes to ensuring safe care. The care produced and consumed results from a complex of relationships, opening space for the occurrence of errors and / or adverse events in the care process. A strong patient safety culture is fundamental to the process of improving patient safety in the hospital setting. It is in this context that the present study asks about how the work factor and its organization are linked to the patient safety culture. The general objective of the dissertation is to analyze the different dimensions of the patient safety culture in the hospital environment. In specific terms, it seeks to identify the relationship between the dimensioning of personnel and the culture of patient safety in the hospital environment. This objective was the focus of the production, entitled "The dimensioning of personnel and the culture of patient safety". The methodology adopted by the dissertation includes a cross-sectional, descriptive study, through stratified probabilistic sampling, with the participation of 239 nursing professionals, including nurses, nursing technicians and attendants, working in a philanthropic hospital in the northern region of the state of Rio Grande do Sul, Brasil. The study uses the Hospital Survey on Patient Safety Culture (HSOPS) questionnaire developed by the Agency for Healthcare Research and Quality (AHRQ) as a basis for data collection and analysis of patient safety culture. The results of these dimensions and the respective assessed items indicate weaknesses in the patient safety culture of the hospital organization under study, especially when analyzing the work overload and the insufficient number of professionals, which involve other weaknesses, such as the passage of duty and patient transfers. Such results are added to the evidence pointed out in the literature about the particularity of the nursing professional's work and the occupational exposures that are inherent to it. The investigation integrates the proposal of the broader project developed in the Graduate Program in Human Aging, entitled "Work, Living and Aging Processes: imbrications between teaching work and the aging of workers". It is part of the research line of the program “Biopsychosocial Aspects of Human Aging”, which aims to articulate different perspectives on the universe of work in an interdisciplinary way.